Impact of sports activities on respiratory function and mechanics in children - Renata Maba Gonçalves; Letícia Goulart Ferreira; Maíra Seabra de Assumpção; Camila Isabel Santos Schivinski
Abstract Introduction: Being physically active in childhood may improve the quality of life in adulthood. So, it is extremely important to evaluate the respiratory function and mechanics of children who participate in sports activities, in order to determine the impact of physical activity on airway resistance. Objective: To analyze measures of respiratory function and mechanics in children who participate (PG) and who do not participate (CG) in sports activities regularly, as well as to compare and correlate the results. Methods: This is a cross-sectional analytical study of healthy school-aged children aged 6 to 12 years, assessed by impulse oscillometry tests (IOS) and spirometry. The sample was divided into PG and CG. The Student's t-Test or Mann-Whitney test was used to compare the groups according to normality of data tested by the Shapiro-Wilk test. The correlation between the tests and age, sex, weight, height and body mass index (BMI) was performed using Pearson's and Spearman correlation coefficient. Statistical data were processed by the SPSS® software, considering significance level at p < 0.05. Results: Forty children participated in the study, 20 in each group, with no differences regarding age, sex, weight, height and BMI. There were significant differences in FEF25-75% (CG: 94.19% ± 13.08 x PG: 101.75% ± 17.44, p = 0.049), and oscillometry data did not differ between both groups. Sex correlated with total airway resistance (R5 - p = 0.049, r = 0.314). Conclusion: In the group with children who participated in sports activities, FEF25-75% was higher, compared to the control group.